Da invisibilidade ao protagonismo: a participação das comunidades quilombolas de Santa Rita no processo de licenciamento ambiental da duplicação da BR-135 e a construção de saberes - CHAVES, Karliane de Jesus Pereira (2023)
This study focuses on the participation of quilombola communities in Environmental Licensing (EL) processes. The implementation of large-scale projects in quilombola territories without any form of consultation, disregarding the entire regulatory framework governing EL procedures, constitutes serious violations of rights under the endorsement of a state that perpetuates colonial and racist practices. Focusing specifically on the BR-135 highway duplication project and guided by the question, “What is the participation of quilombola communities in Santa Rita, Maranhão, in the licensing process for the BR-135 duplication project?”, I observed the dialectical movement between the attempt to silence these communities and the creation of a Committee for the Defense of Rights, which gives voice to these actors historically rendered invisible by the Brazilian state. This project is part of a broader capitalist offensive to promote "development" through a monological logic that erases the presence of traditional communities it affects, treating their historically occupied territories as demographic voids and nature as something separate from social reality. We draw on historical-dialectical materialism to understand the contradictions, the struggle between actors from different social classes, as well as the role of the State in guaranteeing capital expansion. The qualitative research procedures included fieldwork through interviews using a pre-structured guide conducted with formal and informal leaders, field notes, participant observation, and document analysis. In seeking to understand the realities of traditional communities in the context of large projects in Maranhão, we rely on local scholars such as Alfredo Wagner de Almeida (2004), Cíndia Brustolin (2019), Benjamin Alvino de Mesquita (2019), Benedito Souza Filho (2019), and Shiraishi Neto (2019). Analyzing the pedagogical aspect emerging from this context, we engage with Miguel Arroyo’s (2014) concept of “Other Subjects,” recognizing that the organized collective known as the Committee for the Defense of Rights has implemented a range of counter-hegemonic educational practices. These practices highlight the close relationship between social movements and non-formal education, aiming to contribute to the emancipation of quilombola communities, in line with Paulo Freire’s principles. The research results expose the modus operandi of the Brazilian state in favor of agribusiness, while also demonstrating the tangible resistance of the communities through the formation of a new collective — a space for political participation, critical reflection, and popular education within the context of Maranhão.